The Effect on Friction Coefficient and Wear Rate of Palm Kernel Activated Carbon-Epoxy (PKAC-E) Composite at Different Temperatures - Mat Tahir, Noor Ayuma; Abdollah, Mohd Fadzli bin; Hasan, Rafidah; Amiruddin, Hilmi (2014)
The purpose of this study is to investigate the tribological effect on friction coefficient and wear rate of Palm Kernel Activated Carbon-Epoxy (PKAC-E) composite at different temperatures. All specimens were prepared by using compaction technique. The tribological test was carried out by using a pin-on-disc tribometer in dry sliding conditions by applying different temperatures at constant sliding speed and applied load. The worn surfaces were analyzed from the images displayed in Inverted Microscope. The results show that both COF and the wear rate of the composites is increased with temperatures. Some adhesive and abrasive wear types were seen on the worn surfaces.